Optimalisasi Pemberian Hak Karyawan Pasca Pemutusan Hubungan Kerja (PHK) : Studi Kasus PHK di PT Goto Tbk - Amilia, Putri Villa; Alfarizky, Hertasandho Maynaka; Hidayah, Nur; Putri, Amelia Juliana; Susilawati, Siti; Syafri, Muhammad Irvan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Layoffs have been part of the dynamics of industrial relations that have occurred since the past, when work began to be formally organized. In the pre-industrial era, layoffs were hardly recognized because employment relations at that time were based more on the patron-client system, where workers were employed in family-based agrarian or craft systems. However, with the development of the times and the onset of the Industrial Revolution in the 18th and 19th centuries, layoffs began to be more widely recognized. During this time, large corporations that employed many workers saw layoffs as a way to respond to financial pressures or operational efficiencies, albeit often arbitrarily. The situation of workers at that time did not have adequate legal protection, so they could be dismissed arbitrarily and at any time without compensation. Pemutusan Hubungan Kerja (PHK) in the context of Indonesian law refers to the act of terminating the employment relationship between workers and employers. Termination of employment is regulated in Law Number 13 Year 2003 on Manpower and also in other related regulations. According to Article 1 Paragraph 25 of Law Number 13 Year 2003, layoff is “the termination of employment by an employer against a worker/laborer.” Layoffs can occur for various reasons, including company efficiency, bankruptcy, or other reasons stipulated in laws and regulations. Layoffs are a complex issue because they can have an impact on unemployment, crime, and employment opportunities.